Book Production, Importation and Distribution in Iran, Pakistan and Turkey : A Study of Needs with Regional Recommendations within the Context of Social and Economic Development. Preliminary Report, Part I - Barnett, Stanley A.; State Univ. of New York, Stony Brook ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1966)
A nine-week evaluation of developmental book activity in Iran, Pakistan and Turkey, conducted during the summer of 1966 to study existing problems in the preparation, production, importation and distribution of books in these Central Treaty Organization (CENTO) Region Countries, was funded by the United States through the Agency for International Development. The work was carried out in three stages: (1) gathering locally available data on such factors as printing, publishing, library services and resources, etc. in relation to existing programs in human and material resources development; (2) field investigations which concentrated on reviewing current and upcoming book development requirements for economic and educational development in Pakistan and Iran and on updating the"Books as Tools for Turkish National Growth," report in Turkey and (3) utilizing the information gathered from stages 1 and 2 to formulate recommendations and prepare regional and country reports. Because of the limited time allotted to this study, its statistics, at best, represent honest approximations which are considered to be sufficient to indicate present and projected needs and to support reasonable judgments regarding performance and capability. (NH)
Sponsoring Agency: Agency for International Development (Dept. of State), Washington, DC.
Microfiche.
Keywords: Publications; Resource Materials; Books; Developmental Programs; Educational Resources; International Programs; Library Planning; Iran -- Pakistan -- Turkey; Central Treaty Organization (Turkey)